Information Technology in Education - Turaeva Gulchiroy Sheraliyevna (Zien Journals, 2022)
In this article, I have stated howbasic foreign language teaching methods can present the theory of language, their features, and principles. A few imaginative methods of educating might be interactive media, the combination of different computerized media types such as content, pictures, audio and video, into multi-sensory intelligently application or introduction to communicate data to an gathering of people. There are different strategies of teaching.
Keywords: techniques; technology; principles; method